Transvaginal sonographic assessment of follicular development and endometrial thickness in letrozole stimulated cycles of PCOS and non-PCOS infertile women (BIRDEM Medical Journal, 2019)
Background: Infertility in polycystic ovary syndrome (PCOS) is one of the leading causes of anovulatory infertility. Ovulation induction is indicated for the management of anovulatory infertility in PCOS and for augmentation of ovulation in ovulatory infertility, in unexplained infertility. The aim of this retrospective study was to compare and determine the efficacy of letrozole administration in infertile women with PCOS to that of infertile women without PCOS by transvaginal sonography.Methods: This retrospective study was done at Centre for Assisted Reproduction (CARE), BIRDEM General Hospital 2 from January to December 2011. Fifty six infertile women including 16 diagnosed as having PCOS and 40 infertile women with regular menstrual cycle (non-PCOS) were included in this study. Patients were treated with letrozole 7.5 mg/day from day 2-6 of the menstrual cycle. Subjects were monitored once during the days 11 to 14 of the cycle by transvaginal ultrasound. Main outcome measures were number of ovulatory follicles, dominant follicle diameter and endometrial thickness.Results: Letrozole as an ovulation inducing drug was found equally effective in terms of follicular recruitment, follicular maturation and endometrial development both in PCOS and non-PCOS women, as there was no significant difference regarding mature follicular development and endometrial response between the two study groups. Association of endometrial response particularly with follicular diameter 18 mm or more among the study groups revealed no statistically significant difference.Conclusion: In conclusion, our results indicate that the effect of letrozole on endometrial thickness and follicular development in patients of anovulatory PCOS did not significantly differ compared to non-PCOS infertile women.Birdem Med J 2019; 9(3): 234-239